One false note - Korman, Gordon (New York : Scholastic, 2008)
A million dollars, or a clue? Police report a break-in at an elite hotel, and the suspects sound suspiciously like Amy and Dan. There's a car and speedboat chase and an angry mob! When there's a Clue on the line, anything can happen.
Keywords: Ciphers -- Fiction; Treasure hunt (Game) -- Juvenile fiction; Wills -- Juvenile fiction; Family secrets -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Orphans -- Juvenile fiction; Mystery and detective stories; Code and cipher stories; Adventure fiction